2021
DOI: 10.1101/2021.10.21.464743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commensal bacteria promote type I interferon signaling to maintain immune tolerance

Abstract: Type I interferons (IFN) play essential roles in numerous physiological processes, acting as central coordinators in the host response against pathogens. Upon sensing of microbial ligands, host cells rapidly activate the type I IFN response to prime innate and adaptive immune responses. Recent studies suggest tonic IFN are maintained by commensal microbes and critical in mounting an effective immune response to viral pathogens. Further, emerging developments have extended an immunoregulatory role of type I IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Our investigation revealed significant alterations in gene expression signatures due to the absence of a GM in the chicken. In caeca, lungs, and spleen of GF chickens, we observed a substantial reduction in the expression of ISGs, such as IRF1, IFIT, OASL, and MX1, aligning with findings in GF mice 74 .…”
Section: Discussionsupporting
confidence: 87%
“…Our investigation revealed significant alterations in gene expression signatures due to the absence of a GM in the chicken. In caeca, lungs, and spleen of GF chickens, we observed a substantial reduction in the expression of ISGs, such as IRF1, IFIT, OASL, and MX1, aligning with findings in GF mice 74 .…”
Section: Discussionsupporting
confidence: 87%
“…This also includes the IFN gene expression profile in DC (Stefan et al, 2020). Interestingly, some bacterial taxa might harbor a particularly strong ISG inducing activity such as lactobacilli, Blautia coccidioides and the anaerobic commensal bacteria of the Bacteroides species (Ayala, 2021;Kawashima et al, 2018;Kawashima et al, 2013;Stefan et al, 2020;Yang et al, 2021). In our dataset, Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for such diverse roles of type I IFN in bacterial infections are still unclear and require many interdisciplinary studies. Based on research, scientists have shown that bacteria trigger the production of type I IFN mainly by recognizing their nucleic acids or lipopolysaccharide (LPS), which is one of the components of the cell wall [263][264][265]. As a result of the recognition of these PAMPs, innate immune response mechanisms are activated.…”
Section: The Role Of Interferons In the Course Of Bacterial Infectionsmentioning
confidence: 99%
“…As a result of the recognition of these PAMPs, innate immune response mechanisms are activated. The activation pathways of IFN induction mechanisms have been best described for IFN-β, which, according to studies, is among Based on research, scientists have shown that bacteria trigger the production of type I IFN mainly by recognizing their nucleic acids or lipopolysaccharide (LPS), which is one of the components of the cell wall [263][264][265]. As a result of the recognition of these PAMPs, innate immune response mechanisms are activated.…”
Section: The Role Of Interferons In the Course Of Bacterial Infectionsmentioning
confidence: 99%